Strategi Pengembangan Potensi Pariwisata di Pantai Kuri Caddi Desa Nisombalia, Kabupaten Maros - Farah Alivia Yunita Laoh; Agus Salim; Rusneni Ruslan (Journal of Urban Planning Studies, 2021)
This study aimed to identify what factors affecting the development of tourism in Kuri Caddi Beach, Nisombalia Village, Maros Regency. As well as to identify a strategy for developing tourism potential on Kuri Caddi Beach, Nisombalia Village, Maros Regency. The variables used consisted : (1) Tourist Attraction; (2) Supporting Facilities; (3) Safety and Comfort; (4) Information and Promotion; (5) Accessibility; (6) Job Opportunities; (7) (Income). The analytical method used chi-square, likert scale scoring, and SWOT analysis. There were four variables that have effect on the tourism potential development strategy in Kuri Caddi Beach, which are tourist attraction, safety and comfort, job opportunities and income. Meanwhile, there were three variables that have no effect, such us supporting facilities, information and promotion, and accessibility. The strategy that can be used for developing tourism potential on Kuri Caddi Beach is by utilizing the tourist attraction of Kuri Caddi Beach by referring to the Maros Regency Regional Regulation number 2 of 2014, concerning the implementation of tourism, involving the community in developing Kuri Caddi Beach tourism based on the Regional Tourism Development Master Plan, and involves investors in developing Kuri Caddi Beach tourism, so that PAD and local community income are increased.